EXPLORING THE CAUSES OF ACCOUNTING RESISTANCE IN MSME’s THROUGH MULTI STAKEHOLDER PERSPECTIVE - Suryantara, Adhitya Bayu; Ridhawati, Rini; Hanani, Tri (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
Micro, small, and medium enterprises (MSMEs) play a pivotal role in Indonesia’s economy, contributing to economic growth and job creation. However, these businesses often face challenges related to financial reporting. Without proper accounting practices, MSMEs lack clarity regarding their profitability and overall business development. Previous research highlights the unpreparedness of MSME actors as a significant barrier to implementing accounting standards (SAK EMKM). This study investigates the relevance of SAK EMKM for MSMEs by exploring stakeholder perspectives. Data were collected through Focus Group Discussions (FGDs) involving participants from various sectors, including PLUT, DJP Nusa Tenggara, conventional and sharia banking institutions, MSME representatives, and educational accountants. The research reveals that the bargaining value between MSMEs and stakeholders is crucial for accounting adoption. When stakeholders exert stronger influence, coercive isomorphism encourages MSMEs to adopt accounting systems. Conversely, if MSMEs perceive their bargaining power as higher, coercive approaches are less effective. Policy makers and decision makers must actively support an enabling environment for MSMEs, emphasizing the importance of accounting information. By doing so, Indonesia can enhance financial transparency, promote sustainable growth, and empower its vital MSME sector.